AURKA, MAPK14 e genes da via MTOR-MYC-E2F como novos potenciais biomarcadores terapêuticos e de prognóstico para o adenocarcinoma gástrico - Mesquita, Felipe Pantoja (2021)
Gastric cancer is one of the cancer types with the highest incidence and mortality rate in Brazil, especially in the north and northeast of the country, being considered an important public health issue not only in Brazil, but in other countries around the world as well. The treatment of this disease is increasingly restricted and facing problems such as chemoresistance in therapy with currently used chemotherapeutics. With targeted therapy emergence, studies were intensified in recent years, originating new, more selective and effective drugs which are becoming the new generation of chemotherapy for cancer treatment. Phosphorylation is the most important transfer reaction in cellular environment and genes related to kinases encode an important class of proteins involved in this transfer, involved in several cellular processes responsible for tumorigenesis. Currently, kinases are the main targets in targeted therapy. Therefore, the main objective of the present work was to develop a translational study to identify kinase targets as anticancer therapy for gastric cancer. For this, a panel of kinase inhibitors with 367 molecules were tested against gastric cancer strains, and the most cytotoxic inhibitors were selected for mechanism of action characterization. Then, the inhibitors pharmacological targets were measured in clinical specimens to validate the therapeutic potential. Furthermore, a signaling pathway enrichment analysis was performed with a transcriptome dataset comparing gastric tumor and healthy gastric tissue. The results showed that, after the initial kinase inhibitors screening, the main kinase inhibitors with high cytotoxicity were MAPK14 inhibitor (IC50 = 0.91 µM) and the AURKA inhibitors (IC50 ≈ 0,60 µM). The kinase treatment caused cell proliferation decreasing, death by apoptosis inducing, cell migration decreasing and gene expression modulation related to tumor phenotype (P<0.05). Furthermore, MAPK14 (P<0.008) and AURKA (P<0.0001) genes were overexpressed in clinical gastric tumors specimens and significantly correlated with a decrease in the patients’ survival rate (P<0.05). In the enrichment analysis of transcriptome dataset, it was possible to identify the pathways related to the gastric tumoral phenotype: MTORC1_SIGNALING (Enrichment score = 0.60 e p-val = 0.01), MYC_TARGETS_V1 (Enrichment score = 0.72 e p-val = 0.01) e E2F_TARGETS (Enrichment score = 0.73 e p-val = 0.03). Amog the enriched genes within the dataset which are overexpressed in the gastric tumor phenotype and never were mentioned in the literature, we highlighted the HSPE1, PSMD14, and EPRS1 genes. In conclusion, we obtained a list of genes as potential therapeutic targets and/or prognostic biomarkers for patients with gastric cancer, bringing benefits in terms of quality of life and increased survival.